"صعوبات عائشة عبد الرحمن بنت الشاطى": The Challenges of Aisha Abdel Rahman Bint al-Shati DOI:DOI: 10.5281/zenodo.13352467 (Khairulummah, 2024)
The literary Biography deals with the life of the author, and what he has experienced in his life from the troubles and pains to the success, education, and achievements, but at the same time reflects the image of the society in which the writer lived and belonged to, and what this community of social customs and traditions, social and pervasive diseases this can be seen through the events of the writer’s life and his experiences.This article will address the talk about the social and cultural sides of the biography of Ayesha Bent Shati and Her struggle.The writers are characterized by novelty writing, each participatory in various literary arts, including biography, articles, books on political and social ideas, and almost the nature and philosophy of one and only in some ideas.The social aspects include the following topics: family life, family system, Marriage habits, means guardianship of women, love and adoration, polygamy unemployment, illiteracy ignorance, moderation, hospitality, tribal system, and others.